Multiple magnet ingestion in children: A problem on the rise. (16th July 2022) - Seguier‐Lipszyc, Emmanuelle; Samuk, Inbal; Almog, Anastasia; Silbermintz, Ari; Kravarusic, Dragan
Abstract : Aim: Ingestion of multiple magnets is increasing these last 15 years in children. They have resulted in numerous reports of serious gastrointestinal complications such as bowel obstruction, ischaemia, necrosis, perforation and fistula formation and even led to death. The increasing number of world‐wide reports of complications secondary to magnet ingestion and a frequently delayed diagnosis point to a lack of awareness about these risks among medical care‐givers in our country and parents in general. Methods: We reviewed retrospectively all cases of multiple magnet ingestion that required a gastro‐intestinal or surgical procedure for removal from 2009 to 2020. Results: Five children underwent gastroscopy removal and three colonoscopy removal of the magnets. Five patients required surgical (laparotomy or laparoscopy) removal of multiple magnets with intestinal perforations. Conclusions: We propose an updated management algorithm for multiple magnet ingestion to highlight awareness among primary physicians and parents of the presenting circumstances and symptoms as well as the potential complications associated with multiple magnet ingestion.